Perdamaian dalam Perkara Perdata (Upaya Perdamaian di Pengadilan Agama di Indonesia) - Muhammad Irsyad (CERED Indonesia, 2020)
Law Peace efforts in court as a form of implementing a peaceful institution in the court process can be carried out through the Supreme Court Circular No. 1 of 2002 so that all panel of judges who try the case seriously seek peace by applying the provisions of Article 130 HIR / 154 R.Bg, not only for the formality to propose peace, the appointed judge acts as a facilitator who helps the parties in terms of time, place and gathering data and argumentation of the parties in the framework of preparation towards peace. Peace is then consulted with the parties to obtain a win-win solution. The success of the settlement of the case through peace can be used as a material assessment (reward) for judges who become facilitators or mediators. The application of the Peace Institution in the civil litigation process in the court must be further developed, to provide satisfaction for the community seeking justice and in order to limit the case of cassation. First-rate Court Judges in their role as mediators in peaceful institutions, must try to bring and invite the parties to the dispute to discuss together the resolution of disputes and invite them to deliberate, seek and find solutions to solutions that are good and acceptable to the parties.